Longitudinal growth in HIV-negative boys with haemophilia - Lebl, J; Falger, J; Zidek, T; Male, C; Komrska, V; Frisch, H (European journal of pediatrics, 2000)
UNLABELLED: It has been shown that HIV-positive haemophilic children develop growth retardation. As not only the HIV infection but also other disease-related factors might compromise growth in these children, growth data were analysed in a longitudinal cross-sectional manner in 84 HIV-negative haemophilic patients from two university clinics. A total of 2-24 height and weight measurements (median 6) were recorded in each patient resulting in 683 single values collected between 1977-1995. Height SDS of all haemophilic boys was -0.31 +/- 2.13 (mean +/- SD, NS versus 0) and body mass index SDS was 0.21 +/- 3.49 (mean SD, NS versus 0) at first measurement and remained unchanged throughout the observation period. Neither height nor body mass index differed with respect to the severity of haemophilia (mild/moderate/severe) or the study centre (Vienna/Prague). CONCLUSION: Growth in HIV-negative patients with haemophilia is not affected in spite of the immunological abnormalities attributed to the substitution therapy or the bleeding episodes in the joints with the potential effect on the growth plate.
Keywords: tělesná výška; Hemophilia A; mužské pohlaví; Body Mass Index; Male; Humans; HIV séronegativita; HIV Seronegativity; kojenec; lidé; Cross-Sectional Studies; Growth Disorders; lineární modely; Infant; hemofilie A; stupeň závažnosti nemoci; Longitudinal Studies; mladiství; tělesná hmotnost; studie případů a kontrol; poruchy růstu; Case-Control Studies; dítě; Child; Adolescent; Severity of Illness Index; longitudinální studie; Body Weight; Child, Preschool; dospělí; Adult; index tělesné hmotnosti; průřezové studie; předškolní dítě; Linear Models; Body Height